Reconstruction of a time-dependent potential in a pseudo-hyperbolic equation - Tekin, Ibrahim (Politechnica University of Bucharest Splaiul Independentei 313 - Sector 6 Bucharest 77206, 2019)
In this paper, an initial boundary value problem for a pseudo-hyperbolic equation is considered. Giving an over-determination condition, a timedependent potential is determined and existence and uniqueness theorem for small times is proved. Also, theorem of the conventional stability of the solution of the inverse problem is given. © 2019, Politechnica University of Bucharest. All rights reserved.
Keywords: Fourier method; Inverse problem; Pseudo-hyperbolic equation